1997
DOI: 10.1073/pnas.94.17.9463
|View full text |Cite
|
Sign up to set email alerts
|

In vitro repair of oxidative DNA damage by human nucleotide excision repair system: Possible explanation for neurodegeneration in Xeroderma pigmentosum patients

Abstract: Xeroderma pigmentosum (XP) patients fail to remove pyrimidine dimers caused by sunlight and, as a consequence, develop multiple cancers in areas exposed to light. The second most common sign, present in 20-30% of XP patients, is a set of neurological abnormalities caused by neuronal death in the central and peripheral nervous systems. Neural tissue is shielded from sunlight-induced DNA damage, so the cause of neurodegeneration in XP patients remains unexplained. In this study, we show that two major oxidative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
219
0
4

Year Published

2000
2000
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 338 publications
(231 citation statements)
references
References 52 publications
8
219
0
4
Order By: Relevance
“…The large parts of these nonbulky adducts are repaired by the base excision repair (BER) mechanism, 5,10 with possible participation from nuclear excision repair. 11 DNA glycosylases, of which there are several types, recognize damaged DNA bases and catalyze hydrolytic cleavage of the N-glycosyl bond linking the base to the sugar. A DNA polymerase then fills the resulting gap.…”
Section: Introductionmentioning
confidence: 99%
“…The large parts of these nonbulky adducts are repaired by the base excision repair (BER) mechanism, 5,10 with possible participation from nuclear excision repair. 11 DNA glycosylases, of which there are several types, recognize damaged DNA bases and catalyze hydrolytic cleavage of the N-glycosyl bond linking the base to the sugar. A DNA polymerase then fills the resulting gap.…”
Section: Introductionmentioning
confidence: 99%
“…However, in vivo studies revealed a role for NER in the repair of methylated DNA base lesions that do not cause major helical distortions and in providing cellular resistance to simple methylating agents (38,48,49). Indeed, biochemical studies confirmed that subtle types of DNA damage can be substrates for NER, including thymine glycols, 8-oxoguanine, O 4 -ethylthymine, O 4 -methylthymine, O 6 -methylguanine, AP sites, and N 6 -methyladenine (17,22,26,36,38,46). Thus, NER may play a role in alkylation resistance larger than was originally thought.…”
mentioning
confidence: 99%
“…Some adducts are subject to multiple repair pathways (i.e., 8-oxo-dG is repaired by BER and, presumably, NER machinery (23,24)). Etheno adducts bearing structural similarity to M 1 dG (e.g., 1,N 2 -ethenodG, 1,N 6 -etheno-deoxyadenosine, and 3,N 4 -etheno-deoxycytidine) are substrates for BER enzymes and DNA glycosylases (25)(26)(27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%